Pendampingan Pembuatan Hologram 3D Di Kabupaten Igtk Dalam Upaya Pencegahan Dan Pengurangan Dampak Risiko Bencana Gunung Merapi Pada Anak Usia Dini - vivi anggraini; Widya Parikeslan; Alkadri Masnur; Nur Hazizah; Yulsyofriend; Mega Cahya Dwi Lestari; Adi Priyanto; Tia novela (Jurnal Dremi (Demi Pengabdi Masyarakat), 2025)
West Sumatra has an active volcano located in Agam and Tanah Datar districts. Mount Merapi erupted at its peak on Sunday, December 23, 2023. It is known that 23 people died. One person died and 52 were injured. As of Wednesday, March 27, 2024, ESDM Magma Report mention, tall column MountMarapi eruption observed reach 1,500 meters in on peak, or around 4,391 m in on surface sea. Based on data in on importance the community, especially young children, know about Mount Merapi disaster mitigation in the areas Areas such as Nagari Bukik Batabuah and Koto Baru require major preventive measures. namely: 1) knowing the signs that appear before a disaster occurs and how to save yourself self for child age early. 2) Children need introduced factors reason disaster so that when a disaster occurs, the impact of the risk can be reduced. Insight into mitigation disasters, and strengthening disaster mitigation is also a form of implementation of Sustainable Development Goals (SDGs) year 2030 objective to 13. Mitigation disaster on The basic principles can be instilled through education. Communication with the Garden Teachers Association Canduang and X Koto children stated the importance of mentoring teachers in create APE Mitigation disaster